2017
DOI: 10.1002/jbmr.3096
|View full text |Cite
|
Sign up to set email alerts
|

VDR in Osteoblast‐Lineage Cells Primarily Mediates Vitamin D Treatment‐Induced Increase in Bone Mass by Suppressing Bone Resorption

Abstract: Long-term treatment with active vitamin D [1a,25(OH) 2 D 3 ] and its derivatives is effective for increasing bone mass in patients with primary and secondary osteoporosis. Derivatives of 1a,25(OH) 2 D 3 , including eldecalcitol (ELD), exert their actions through the vitamin D receptor (VDR). ELD is more resistant to metabolic degradation than 1a,25(OH) 2 D 3 . It is reported that ELD treatment causes a net increase in bone mass by suppressing bone resorption rather than by increasing bone formation in animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…Transgenically overexpressed VDR in mature osteoblast-lineage cells in mice also increased bone mass by suppressing bone resorption ( 24 , 25 ). These antiresorptive effects were not observed in Ob-VDR-cKO mice ( 30 ). Thus, the proresorptive action and the antiresorptive action of bioactive vitamin D are mediated by VDR in osteoblast-lineage cells.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Transgenically overexpressed VDR in mature osteoblast-lineage cells in mice also increased bone mass by suppressing bone resorption ( 24 , 25 ). These antiresorptive effects were not observed in Ob-VDR-cKO mice ( 30 ). Thus, the proresorptive action and the antiresorptive action of bioactive vitamin D are mediated by VDR in osteoblast-lineage cells.…”
Section: Discussionmentioning
confidence: 86%
“…We confirmed that eldecalcitol administration increased bone mass by suppressing bone resorption via downregulation of the RANKL/OPG ratio in bone tissues without affecting the number of osteoclast precursors ( 29 ). To clarify which type of VDR-expressing cells preferentially regulated the eldecalcitol-induced increase in bone mass, we generated osteoblast-lineage (osteoblast and osteocyte)-specific VDR conditional knockout [Ob-VDR-cKO, osterix (Osx)-Cre Tg/0 ; VDR fl/fl ] and osteoclast-specific VDR-cKO [Ocl-VDR-cKO, cathepsin (Ctsk) Cre/+ ; VDR fl/fl ] mice ( 30 ). Administration of eldecalcitol for 4 weeks neither suppressed bone resorption nor increased bone mass in Ob-VDR-cKO mice ( 30 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1α,25-Dihydroxyvitamin D3 (1,25D3) is the most active metabolite of vitamin D3 and plays a major role in the enhancement of bone formation [10]. 1,25D3 exerts its actions via binding with and modulating the vitamin D receptor (VDR), a transcriptional regulator [11][12][13]. 1,25D3 also activates Wnt/β-catenin to facilitate osteoblast differentiation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%